NANOPARTICLES USED FOR THE TREATMENT OF DIABETES - SRIDHAR, SURBHI; SINGH, AJEET PAL; SINGH, AMAR PAL (International Journal of Current Pharmaceutical Research, 2026)
The worldwide health crisis caused by diabetes mellitus calls for novel therapeutic solutions because traditional treatments have shown their limitations. The review conducts an in-depth evaluation of nanoparticle-based technologies within diabetes care. For this, their functions in drug transport optimization and enhanced substance distribution, along with prolonged blood sugar stabilization capabilities, are examined and investigated. Different types of nanoparticle platforms, which include polymeric, lipid-based, inorganic, and natural nanoparticles, have shown excellent achievements in both preclinical research and clinical practice by delivering targeted drugs while minimizing adverse effects alongside glucose-triggered insulin release. The review explains how smart insulin delivery methods, along with anti-inflammatory care and personalized nanomedicine solutions, have progressed; however, it details the barriers that exist for biocompatibility and regulatory requirements and large-scale production. Laboratory research shows that nanotechnology has great potential for diabetes treatment through independent glucose control systems and simplified drug delivery processes, leading to better healthcare results. Nanoparticles offer promise to achieve disease modification rather than symptom management, even though their production requires solutions, and their long-term effects need further investigation. Nanomedical research should concentrate on maximizing smart nanoparticulate development while creating scalable manufacturing processes and developing patient-customized therapy models to establish nanomaterials fully in diabetes treatment practice.